Development of the Heart Muscle after Antenatal Ethanol Intoxication during the Neonatal Period (Bangladesh Journal of Medical Science, 2022)
Objective: The aim of the study was to study the effect of antenatal ethanol intoxication on the postnatal development of the heart muscle during the neonatal period.Materials and methods: The experiment was carried out on 24 pregnant female rats weighing 180-200 grams. The animals were divided into 2 groups: experimental and control. 12 animals of the experimental group were injected with a 30% ethanol solution from 6 to 21 days of gestation daily, once, endogastrically, at a dose of 5 g / kg. The animals of the control group were injected with the same volume of physiological saline.Results and Discussion: On the 1st and 7th days after birth, the rat pups were killed by decapitation under light ether anesthesia. After determining the mass of the heart, part of the organ was studied electron microscopically, part was fixed in 10% neutral formalin, then histological preparations were prepared in accordance with standard methods. Sections were stained with hematoxylin and eosin. The nuclear-cytoplasmic ratio in cardiomyocytes, the specific density of the capillary network of the myocardium, and the specific density of cardiomyocytes were measured. The data obtained were statistically processed.Conclusion: The study showed that antenatal ethanol intoxication has a pronounced effect on the postnatal development of the heart muscle during the neonatal period, which manifests itself at the cellular and subcellular levels. The value of the obtained results lies in the fact that for the first time ultrastructural changes in postnatal development in the neonatal period of the fetal heart muscle during prenatal ethanol intoxication are shown at the electron microscopic level.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 344-353